Microsynthetics in waters of the South American Pantanal - De Faria, Érika; Girard, Pierre; Gomes Camargo, Alan Lacerda; Moreschi Silva, Andressa Carla; Christo, Susete Wambier; Casado Coy, Nuria; Sanz-Lazaro, Carlos; Costa, Monica Ferreira (Frontiers in Environmental Science, 2022)
Microplastics are an emerging global threat to freshwater ecosystems. There is a growing number of microplastic studies in wetlands and floodplains such as the Pantanal. Microplastics in the Pantanal’s water courses, lakes, and floodplains were sampled with a plankton net in 16 locations in the Pantanal lowlands at varying distances from their potential urban sources over 2 years. Microplastics from the water samples were separated from sediments and organic matter and examined under a stereomicroscope to be identified and counted. Visual determination was then confirmed by RAMAN spectrometry. We found 730 microplastics. The average ± std microplastic concentration was 38 ± 16 x/m3, ranging between 10 and 100 x/m3. Fibres, fragments, and films represented 68%, 28%, and 4%, respectively, of the total microplastics. Surprisingly, a synthetic blue fibre of non-identified composition accounted for 51.0% of the microplastics. Other identified polymers included PP (18.2%), PET (16.9%), PVC (5.1%), PVA (4.4%) and LDPE (4.4%). The blue fibres, PP, and PET were found at all sampling locations. Microplastic concentrations varied from 27 ± 12 x/m3 to 48 ± 21 x/m3 across the sampling sites. Microplastics’ average size was 0.51 ± 0.21 mm, ranging from 0.06 to 0.97 mm. In the study area, the average seasonal concentrations varied from 34 ± 11 to 43 ± 18 x/m3 during the 2 years study period (2018–2019). In lentic environments, the median concentrations (30 x/m3) were significantly lower than in the lotic ones (40 x/m3). Urban human activities are a potential source of microplastics as the concentration of these increased significantly with the population of the nearest human agglomeration. These results indicate widespread contamination of the Pantanal waters by microplastics. Furthermore, a microsynthetic of indeterminate composition is found everywhere in the Pantanal, and more research is urgently needed to determine its composition and sources. The contamination by micropolymers and other microsynthetics will likely impact the Pantanal biota and, eventually, humans living in these floodplains.